Literature Companion - Draze, Dianne (San Luis Obispo Dandy Lion Publications, 1989)
More and more teachers are incorporating literature into their basic reading program. They are realizing that literature offers an opportunity to not only teach the basics of reading but also to instill a love of reading. Literature Companion is a versatile guide that offers a wide range of activities that will aid students in meeting this goal. Worksheets are open-ended, so they can be used with any books as either group exercises in a literature unit or as individual book reports.
Keywords: Children Literature